Mechanical Design of DNA Origami in the Classroom - Yuchen Wang; Anjelica Kucinic; Lilly Des Rosiers; Peter E. Beshay; Nicholas Wile; Michael W. Hudoba; Carlos E. Castro (Applied Sciences, 2023)
DNA origami (DO) nanotechnology has strong potential for applications including molecular sensing, drug delivery, and nanorobotics that rely on nanoscale structural precision and the ability to tune mechanical and dynamic properties. Given these emerging applications, there is a need to broaden access to and training on DO concepts, which would also provide an avenue to demonstrate engineering concepts such as kinematic motion and mechanical deformation as applied to nanotechnology and molecular systems. However, broader use in educational settings is hindered by the excessive cost and time of fabrication and analysis. Compliant, or deformable, DO is especially difficult to design and characterize in a cost-effective manner, because analysis often relies on advanced imaging methods to quantify structure conformations. Building on recent work establishing classroom-ready methods for DO fabrication and analysis, we developed an experiment module for classroom implementation focused on a DO compliant hinge joint. The module consists of folding three distinct joint conformations that can be evaluated via gel electrophoresis using portable and cost-effective equipment within ~120 min. To highlight the mechanical design, we present two beam-based models for describing the deformation that controls the joint angle. We envision that this module can broaden access to and interest in the mechanical design of DO.